Analysis of Cross‐Rate Interference Cancelation by Use of a Novel Phase Code Interval in Loran Navigation System. Issue 3 (28th August 2017) - Bayat, Meysam; Madani, Mohammad Hossein
Abstract: This work concentrates on improving performance of the Loran system with rejection of cross‐rate interference (CRI) by the use of a new phase code interval, the so‐called Bayat Phase Code Interval (BPCI), and on the signal in the frequency domain. Indeed, interference will be canceled by removing the common spectral lines between main and interference chains in all integer coefficients of the greatest common divisor frequency of two code intervals. In addition, all interference originating from sky waves that have delay greater than 700 μs is removed by employing both the presented phase code and averaging algorithm. The results demonstrate that if the design is desirable, in the sense that the inverse of the greatest common divisor of BPCI of the considered chain with adjacent interfering chains is equal to an integer multiple of 0.5 kHz, then the proposed BPCI rejects all of the spectral lines of the undesired chain. Copyright © 2017 Institute of Navigation